The Impact of Artificial Intelligence on the Accounting Profession: A Concept Paper - Hussin, Nurul Afza Khusaini Mat; Bukhari, Nurul Ain Nadiah Mohd; Hashim, Nurul Hani Azyyati Nor; Bahari, Sharina Nur Azyyati Shaipul; Ali, Mazurina Mohd (Business Management and Strategy, 2024)
This study examined the impact of artificial intelligence (AI) on the accounting profession. It systematically investigated the effects of AI technologies on the accounting field, redefining the roles and responsibilities of accountants. Through literature review, this study sheds light on AI influence on the accounting profession. The results of this study indicate that the impact of AI on accounting profession can be divided into three themes: (i) automation of routine tasks, (ii) enhanced data analysis, and (iii) value-adding of the professional roles. The automation of routine tasks includes data entry, validation, and transaction processing, while enhanced data analysis includes predictive analytics and decision support. AI also has impacted in terms of value-adding of the professional roles, which comprise of increasing scalability and cost savings and focus on higher value activities. The findings of this study suggest that the accounting profession is evolving in response to AI technology, and accountants should embrace these changes to harness the full potential of AI in their work.